Two lectures by Friedman: One famous, one good - Forder, J (Fabrizio Serra editore, 2019)
Friedman’s Presidential Address to the American Economic Association is compared to a slightly later lecture he gave to the American Philosophical Society. The earlier piece is found to be poorly structured, badly argued, and full of clear mistakes. The later one, although pursuing the same objectives, is in every way much better crafted. It is noted that the earlier one is however much more highly cited, and it is suggested that this means, inter alia, that the large number of citations of the Presidential Address do not reflet much reading of it.